PESAN DAKWAH DALAM TRADISI KENDURI KEMATIAN MASYARAKAT SUKU JAWA DI DESA SIPARE-PARE TENGAH KABUPATEN MARBAU KABUPATEN LABUHANBATU UTARA “STUDI KENDURI KEMATIAN HARI KE-4O” - Muktaruddin Muktaruddin; Nurhalimah Nurhalimah; Qurnia Aini Bay (STIT AL-AMIN KREO TANGERANG, 2021)
Dakwah aims to spread the teachings of Islam to the people and let people know more And the teachings of Islam. Death in any culture is almost certainly accompanied by ritual events. One of the traditions of the archipelago comes from the Javanese tribe, namely the kenduri tradition. When a Javanese person dies, a 40-day death feast will be held. The emergence of religion makes ancestral traditions used as a medium for delivering Da'wah messages. This study aims to analyze the da'wah message contained in the 40 day death feast tradition in the people of the Sipare- pare Tengah Village. This type of research is a qualitative research using descriptive methods. This research was conducted in the Siparepare Tengah Village, Marbau District, North Labuhanbatu Regency. The objects studied are the Javanese people of the Sipare- pare Tengah Village who still carry out the death feast. The community's view on the death feast tradition in the village of Sipare- pare Tengah, is conveyed through the food symbol, the message conveyed is related to the message to always pray for others and remember death.